1984
DOI: 10.1037/0022-0663.76.3.478
|View full text |Cite
|
Sign up to set email alerts
|

Achievement attributions and self-instructions under competitive and individualistic goal structures.

Abstract: The purpose of the study was to determine if competitive and individualistic goal structures elicit achievement cognitions that have been associated with helpless versus mastery-oriented children, respectively. Fifth-and sixthgrade children performed at a high or low level on a novel achievement task within either a competitive or individual goal structure. A "thought-matching" methodology was used to assess the type and frequency of children's thoughts. Results revealed that children made more ability attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
225
1
20

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(259 citation statements)
references
References 23 publications
13
225
1
20
Order By: Relevance
“…We draw on findings from experimental studies to suggest that students' use of learning strategies may be related to whether students adopt a mastery or performance goal orientation in the classroom. In experimental studies, students have reported using more self-instructions and self-monitoring strategies in conditions rewarding or emphasizing self-improvement rather than social comparison (Ames, 1984b) and when they believed in the efficacy of effort (Bandura & Schunk, 1981;Diener & Dweck, 1978;Schunk & Cox, 1986). Similarly, recent theoretical formulations suggest that students are more likely to think about how to do the task when they are oriented toward learning (Nicholls, 1979(Nicholls, , 1984Nolen, 1987) or focused on their own degree of mastery (Ames, 1984b;Covington & Omelich, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We draw on findings from experimental studies to suggest that students' use of learning strategies may be related to whether students adopt a mastery or performance goal orientation in the classroom. In experimental studies, students have reported using more self-instructions and self-monitoring strategies in conditions rewarding or emphasizing self-improvement rather than social comparison (Ames, 1984b) and when they believed in the efficacy of effort (Bandura & Schunk, 1981;Diener & Dweck, 1978;Schunk & Cox, 1986). Similarly, recent theoretical formulations suggest that students are more likely to think about how to do the task when they are oriented toward learning (Nicholls, 1979(Nicholls, , 1984Nolen, 1987) or focused on their own degree of mastery (Ames, 1984b;Covington & Omelich, 1984).…”
mentioning
confidence: 99%
“…There is, in fact, considerable research evidence that situational demands can affect the salience of specific goals, which results in differential patterns of cognition, affect, and performance (e.g., Ames, 1984b;Ames, Ames, & Felker, 1977;Covington, 1984;Covington & Omelich, 1984). For example, when social comparison has been made salient, students have focused on their ability, and these self-perceptions have mediated performance and affecThis research was supported by a grant from the Research Board of the University of Illinois at Urbana-Champaign.…”
mentioning
confidence: 99%
“…Key words: teachers' and pupils' beliefs concerning assessment, pupils' perception of teachers' beliefs, formative and normative pupils assessment Introduction depuis trois décennies, l'un des enjeux majeurs de la recherche en psychologie de l'éducation est de savoir comment et dans quelle mesure les pratiques évaluatives infléchissent la motivation et les apprentissages scolaires (ames, 1984;Brophy & Good, 1970;Butler, 1987;crooks, 1988). un certain nombre de travaux ont montré que les orientations motivationnelles et les stratégies d'apprentissage des élèves varient selon les contextes évaluatifs (Butler, 1987;eccles, wigfield, Midgley, Mac iver & Feldlaufer, 1993;elliot & dweck, 2005;Galand & Grégoire, 2000;stipek, 1993).…”
Section: Cet Article S'inscrit Dans La Foulée Des éTudes Qui Soutiennunclassified
“…In general, motivation has long been linked to perceived efficacy, achievement expectancy, achievement goals and reward (e.g. Atkinson, 1964;Wigfield & Eccles, 2000;Bandura, 1986;Schunk, 1991;Ames, 1984;Dweck, 1986;Maehr, 1984;Nicholls, 1984;Kaplan, Middleton, Urdan, & Midgley, 2002). Hence, it is not surprising that one of the most prominent characteristics of struggling readers is their low motivation for reading-lack of initial drive-impacting their self-perception that ultimately hinder their enjoyment and valuation of self-initiated reading activities (e.g.…”
Section: The Role Of Motivation In Reading Instruction and Learningmentioning
confidence: 99%